Pengaruh Pengendalian Internal, Audit Internal dan Good Corporate Governance terhadap Pencegahan Fraud - Saputra, Andika Dwi; Rosharlianti, Zulfa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of internal control, internal audit and good corporate governance on fraud prevention. This type of research is quantitative research, using associative methods and primary data in the form of a questionnaire which is then processed using the SPSS 29 application. The population in this research is all employees who work at PT. ABC with a total of 70 respondents. The sampling method in this research uses a saturated sample method. The results of this research indicate that the variables of internal control, internal audit, and good corporate governance simultaneously influence fraud prevention. Meanwhile, internal control variables partially influence fraud prevention, internal audit has no influence on fraud prevention, and good corporate governance has no influence on fraud prevention.